The Impact of Foreign Policy on Indonesia’s International Trade: An Empirical Analysis for the 2010-2025 Period - Feri Irawan; Hamdan Hamdan; Irawati Irawati; Nurhayati Nurhayati (Economica Insight, 2026)
This study analyzes the impact of Indonesia’s foreign policy on international trade performance during the 2010-2025 period. The primary focus of the research is to examine how economic diplomacy orientation, international trade agreements, and global geopolitical dynamics influence Indonesia’s exports, imports, and trade balance. The study employs a quantitative approach using secondary data analysis sourced from official government publications and international institutions, complemented by a qualitative approach to strengthen empirical interpretation. The findings indicate that proactive foreign policy through economic diplomacy and participation in regional and bilateral trade agreements contributes positively to increasing trade volume and diversifying Indonesia’s export markets. However, global uncertainty and geopolitical tensions remain significant challenges affecting the stability of Indonesia’s international trade.